2021
DOI: 10.3390/su132413983
|View full text |Cite
|
Sign up to set email alerts
|

Can Corporate Digitalization Promote Green Innovation? The Moderating Roles of Internal Control and Institutional Ownership

Abstract: This study examined the impact of corporate digitalization on green innovation using data concerning A-share companies listed on the Shanghai and Shenzhen stock markets from 2012 to 2018. We measured the degree of corporate digitalization through a text analysis of annual reports and empirically tested its impact on green innovation using a panel data fixed effects model. We found that digital transformation can improve green innovation levels, especially when internal control is weak and institutional ownersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 84 publications
(115 reference statements)
4
73
0
1
Order By: Relevance
“…Through empirical research, Wang et al found that the improvement of digitization level will effectively enhance the technology integration ability of enterprises, thus promoting the green technology innovation activities of resource-based enterprises [23]; Song et al, taking heavily polluting enterprises as the sample, found that enterprise digitization mainly promoted enterprise green technology innovation by improving the enterprise information-sharing level and knowledge integration ability [24]. Li and Shen found that digital transformation significantly promoted green innovation, and its promotion effect was more obvious in enterprises with poor quality of internal control and low shareholding of institutional investors [25]. The other holds that digital transformation does not significantly promote green technology innovation.…”
Section: Research On Digital Transformation and Enterprise Green Tech...mentioning
confidence: 99%
“…Through empirical research, Wang et al found that the improvement of digitization level will effectively enhance the technology integration ability of enterprises, thus promoting the green technology innovation activities of resource-based enterprises [23]; Song et al, taking heavily polluting enterprises as the sample, found that enterprise digitization mainly promoted enterprise green technology innovation by improving the enterprise information-sharing level and knowledge integration ability [24]. Li and Shen found that digital transformation significantly promoted green innovation, and its promotion effect was more obvious in enterprises with poor quality of internal control and low shareholding of institutional investors [25]. The other holds that digital transformation does not significantly promote green technology innovation.…”
Section: Research On Digital Transformation and Enterprise Green Tech...mentioning
confidence: 99%
“…A few scholars have studied the impact of digital technologies on green innovation, but these studies are relatively dispersed, mainly in terms of digitalization, blockchain, Internet, and big data. First, existing studies believe that digital technologies can alleviate the problem of enterprise information asymmetry, improve the level of information sharing [ 53 ], push the integration of R&D resources and knowledge, help to enhance the innovation vitality of enterprises [ 30 ], optimize the allocation of green R&D resources, and, thus, promote green innovation of enterprises [ 76 ]. For instance, Li and Shen (2021) found that digitalization could improve the level of green innovation, especially in the case of imperfect internal control and institutional ownership [ 76 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, existing studies believe that digital technologies can alleviate the problem of enterprise information asymmetry, improve the level of information sharing [ 53 ], push the integration of R&D resources and knowledge, help to enhance the innovation vitality of enterprises [ 30 ], optimize the allocation of green R&D resources, and, thus, promote green innovation of enterprises [ 76 ]. For instance, Li and Shen (2021) found that digitalization could improve the level of green innovation, especially in the case of imperfect internal control and institutional ownership [ 76 ]. Using the survey data of 215 enterprises, El-Kassar and Singh (2019) found that digitalization positively affected enterprise green innovation activities, thereby affecting enterprises’ competitive advantages [ 77 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Better social responsibility can also help enterprises obtain funds to improve production technology and service quality, so as to improve their market competitiveness and increase shareholders’ wealth [ 18 ]. From the perspective of corporate governance, corporate governance factors such as a good management system [ 19 ] and internal control level [ 20 ] significantly encourage green innovation.…”
Section: Literature Reviewmentioning
confidence: 99%